(untitled) (Revista LIDER, 2020)
This article analyzes the current policy of solid waste management in the city of Natal, Brazil. It is the result of a doctoral research finished in 2010, and a research project started in 2013 on recycling in Natal. The results summarize information collected from interviews with recyclable material separators and public managers of Natal and other sources and official information given. In Natal, the Municipality has been using elements of socio-environmental speech to justify the economic actions of its waste management, according with the Brazilian political axes for residues. This practice is configured as an official economic environmentalism, which strives to ensure the reproduction model of final waste through the use of socio environmental discourse